THE EFFECT OF SERVICE, PRODUCT QUALITY, AND PERCEIVED VALUE ON CUSTOMER PURCHASE INTENTION AND SATISFACTION - Dodi Iskandar; Rita Nurmalina; Etty Riani (Indonesian Journal of Business and Entrepreneurship (IJBE), 2015)
The research was conducted at Kedai Sop Durian Lodaya (KSDL) in Bogor on February 2015. The research objectives were 1) to identify the characteristics of KSDL consumer’s behavior, 2) to analyze the factors influencing the consumer satisfaction and purchase intention of KSDL’s consumers , 3) to analyze KSDL's consumer satisfaction level and purchase intention, 4) to formulate the managerial implications in order to increase consumer satisfaction and KSDL's purchase intention. The research was conducted by using descriptive methods through case study approach. Data was collected through questionnaires with non-probability sampling technique, using  convenience sampling technique. Data was analyzed by using Structural Equation Modeling (SEM). The result shows that all of the satisfaction component variabels have significantly influenced consumer satisfaction and purchase intention. In sequence, the variables having the highest influence to the lowest influence are product quality, responsiveness, assurance, empathy, reliability, tangibility, and perceived value.    Keywords: consumer satisfaction, service quality, product quality, purchase intention, SEM, kedai sop durian lodaya (KSDL) ABSTRAKPenelitian dilakukan di Kedai Sop Durian Lodaya (KSDL) di Bogor pada bulan Februari 2015. Tujuan dari penelitian ini adalah 1) mengidentifikasi karakteristik perilaku konsumen di KSDL, 2) menganalisis faktor-faktor yang mempengaruhi kepuasan dan purchase intention pada konsumen di KSDL, 3) menganalisis tingkat kepuasan dan purchase intention konsumen di KSDL, 4) merumuskan implikasi manajerial untuk meningkatkan kepuasan konsumen serta menimbulkan purchase intention konsumen di KSDL. Penelitian ini dilakukan dengan metode deskriptif melalui pendekatan studi kasus. Pengumpulan data dilakukan melalui pengisian kuesioner dengan teknik nonprobability sampling menggunakan metode convenience sampling. Data dianalisis dengan menggunakan structural equation modeling. Hasil analisis Structural Equation Modeling (SEM) menunjukkan bahwa semua variabel penyusun kepuasan berpengaruh signifikan terhadap kepuasan konsumen dan purchase intention. Secara berurutan pengaruh dari yang paling besar sampai yang terkecil adalah product quality, responsiveness, assurance, emphaty, reliability, tangible, dan perceived value. Kata kunci:  kepuasan konsumen, service quality, product quality, purchase intention, SEM,kedai sop durian lodaya (KSDL)